Gluten Sensitivity, IBS & Homeopathy (Homoeopathy for All, 2024)
In the current times, irritable bowel  syndrome (IBS) has become one  of the most frequently identified  digestive disorders. It is a symptom based condition that can be identified  by the presence of abdominal pain or  discomfort together with abnormal  bowel habits in the absence of any  other underlying disease that would  be responsible for these symptoms.  Patients report chronicity of  complaints experiencing stomach  pain and abnormal bowel habits,  primarily with constipation  (IBS-C), diarrhoea (IBS-D), or mix  of both (IBS-M). IBS is diagnosed  clinically because there hasn't been  a conclusive investigation or any  specific biomarker for its diagnosis.
Keywords: syndrome; abdominal; diagnosis